Die waarde van spel in die opvoedingsproses - De Jager, A. M. (University of the Free State, 1998)
This study regarding children's play and games commences with the study thereof. It is interesting to note that pedagogues and spiritual leaders already acknowledged the value of play and games at a very early stage. Thus they have pleaded for and exerted themselves in favour of the recognition of play and games as essential activities for the total development of the child. There have been some who regarded play as unnecessary and time-consuming. According to this literature study concerning children's play and games, many researchers already completed their studies, while others are still researching the subject to determine what play really is: Which value does play have for the child? What is necessary to make the child participate in play and games? To which extent is the child influenced by his play environment? It is virtually impossible to mention all the advantages of play. Certain values are discussed in this dissertation, e.g. the socialisation of the child, as he cannot develop fully without other individuals. There are various relationships which can develop by means of play. In the first place there is the relationship of the family which must be developed, followed by the relationship between one child and another, as well as the relationship between the pupil and the teacher. All of these lead to the building of societal relationships. A child is sometimes in need of play on his own. This is of great importance, as the child gets to know himself and learns to occupy himself. Territorial play is closely related to sole play. It is extremely important for the development of the child to have experience of appropriating a territory or an area, however small, for himself. Independence and a sense of responsibility are developed spontaneously by means of play. The parents must merely provide the necessary opportunities for play, as well as stimulating and safe play environments. If these precautionary measures are adhered to, the emotional and physical development of the child will take place naturally. If children are hampered in their play, it can lead to the necessity to undergo therapeutic treatment. During the course of this treatment the child's play is of extreme importance, because play is the natural method of communication of the child. By means of play his problems can become clear to an observer, because in his play he expresses his feelings, whether they be positive or negative. Play is extremely valuable, as a child learns more easily by play than through formal teaching. Various researchers in this field have proved that play can be a useful method of learning, for example mathematics. Education therefore has a medium available which can and must still be researched extensively. "Education - which is the promotion of growth, child culture - will include teaching both in school and on the playground" (Lee, 1942:40). Playgrounds provide the space for extramural activities - which include play - which can be an extension of the classroom education. This is the place where the child develops as a whole. The principal and the teacher have opportunities which are not always available in the classroom. On the playground the child's needs are satisfied and spiritual growth takes place as a result of his relationship with other children, with the teacher, as well as with the principal (if he has the right attitude). The principal who serves as a role model, will never be able to fully judge the value of the influence which he has on the pupils. Furthermore, it is by means of extramural activities that the child learns to fully utilise his leisure time. The parents play a very important role in the development of the child through play. Before the child goes to school, his development is the responsibility of the parent. When he goes to school, the parent shares this important responsibility with the teacher. The parent has an incredibly great influence on the child's attendance of extramural activities. Thus it is also the duty of the parent to see to it that the child utilises his leisure time in a meaningful and fruitful manner, because this experience accompanies a child into his adulthood. It causes a parent extreme satisfaction to observe the golden thread of the value of play in the whole of his child's life, especially as he himself lay the foundation.

Dié studie rakende kinderspel het begin met die geskiedenis van kinders se spel. Dit is interessant dat opvoedkundiges en geestelikes reeds baie vroeg die waarde van spel erken het. Die bogenoemdes het dan gepleit en hulle beywer vir die erkenning van spel as 'n noodsaaklike aktiwiteit om die kind in sy totaliteit te laat ontwikkel. Daar was ook diegene wat spel as onnodig en as 'n tydverspillende aktiwiteit beskou het. Volgens hierdie literatuurstudie rakende kinderspel het baie navorsers reeds studies voltooi, terwyl baie steeds besig is met navorsing betreffende wat spel nou eintlik is; van watter waarde spel vir die kind is; wat nodig is om die kind aan spel te laat deelneem; asook in hoeverre die kind deur sy spelomgewing beïnvloed word. Dit is haas onmoontlik om al die voordele van kinderspel te noem. Enkele waardes word in die verhandeling uitgelig, byvoorbeeld die sosialisering van die kind, aangesien hy nie sonder ander persone ten volle kan ontwikkel nie. Daar is verskillende verhoudinge wat deur middel van spel kan ontwikkel. Ten eerste is dit die verhoudinge in die huisgesin wat ontwikkel moet word deur spel. Daarna volg die kind-tot-kindverhouding en die kind-onderwyserverhouding, wat uitbrei tot gemeenskapsverhoudinge. Die kind het somtyds behoefte aan alleenspel. Dit is van groot belang vir die kind om alleen te speel, homself te leer ken en te leer om homself besig te hou. Gebiedspel hang baie nou saam met alleenspel. Vir die kind se ontwikkeling is dit uiters belangrik dat hy die ervaring moet hê om 'n gebied, al is dit baie klein, vir homself te kan toeeien. Onafhanklikheid en verantwoordelikheidsin ontwikkel spontaan deur spel. Die ouers moet net sorg vir die nodige geleenthede om te kan speel, asook die verskaffing van stimulerende en veilige speelomgewings. Met hierdie voorsorgmaatreëls sal die kind se emosionele en fisiese ontwikkeling normaal geskied. Wanneer kinders in hulle spel gestrem word, kan dit lei tot die noodsaaklikheid vir terapeutiese behandeling. Ook in hierdie behandeling speel die kind se spel 'n uiters belangrike rol, want spel is die natuurlike kommunikasiemiddel vir 'n kind. Deur spel kan sy probleme vir die waarnemer duidelik word, want dit is in sy spel dat hy uiting gee aan sy gevoelens, hetsy negatief of positief. 'n Baie groot waarde van spel is geleë in die feit dat 'n kind makliker leer deur middel van spel as deur formele onderrig. Op hierdie gebied het verskeie navorsers bewys dat spel as 'n nuttige metode kan dien, soos in die voorbeeld om wiskunde deur middel van spel aan te leer. Die opvoeding het dus 'n medium wat nog baie nagevors kan en moet word. "Education - which is the promotion of growth, child culture - will include teaching both in school and on the play-ground" (Lee, 1942: 40). Speelgronde bied die terrein vir buitemuurse aktiwiteite - wat spel insluit - wat kan dien as 'n verlengstuk van die klaskameropvoeding. Dit is hier waar die kind in sy totaliteit ontwikkel. Die skoolhoof en die onderwyser kry geleenthede wat nie in die klaskamer altyd moontlik is nie. Die kind ontvang hier bevrediging vir sy behoeftes, asook geestelike groei deur verhoudinge met ander kinders, die onderwyser en die skoolhoof met die regte gesindheid. Die skoolhoof wat dien as 'n rolmodel, sal nooit die invloed wat hy op die leerlinge het, ooit na waarde kan skat nie. Dit is ook in die buitemuurse aktiwiteite dat die kind leer hoe om sy vrye tyd nuttig te benut. Die ouers speel 'n belangrike rol in die kind se ontwikkeling deur middel van spel. Voordat die kind in die skool is, is die kind se ontwikkeling die ouer se verantwoordelikheid Wanneer die kind skool toe gaan, deel die ouer dié belangrike verantwoordelikheid met die onderwyser. Die ouer se invloed op die kind vir deelname aan buitemuurse aktiwiteite is onberekenbaar. So ook is dit die ouer se plig om toe te sien dat die kind sy vrye tyd nuttig en vrugbaar benut, want hierdie ondervinding neem hy saam met hom tot in sy volwassenheid. Met groot genoegdoening kan die ouer die waarde van spel, waarvan hy die basis gelê het, deur die kind se ganse lewe as 'n goue draad geweef sien.
Dissertation (M.Ed. (Education))--University of the Free State, 1998
Keywords: Play -- Psychological aspects; Child development; Education, Elementary